Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/s1002-0160(15)60045-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Use Efficiency of Bio-Based Fertilizers: Bioavailability and Fractionation

Abstract: Although to date some technologies producing bio-based phosphorus (P) fertilizers have been proposed and implemented, the efficient use of the recovered products is still limited due to legislative constraints, lack of insights in their P release with time, and in the corresponding mechanisms. The aim of this paper was to evaluate the fertilizer performance in terms of P release and use efficiency of recovered struvite, iron phosphate (FePO4) sludge, digestate, and animal manure as compared to fossil reserve-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 49 publications
1
43
0
3
Order By: Relevance
“…An earlier study by Antille et al (2014b) showed that relative extractability (Leytem et al, 2004) of OMF P was between 3 and 12%, which suggested only a small proportion of total P applied as OMF is released in plant-available form (Olsen P) within the first season. The remaining OMF P may be released over several years following soil application, as shown in related studies involving biosolids P (e.g., Kelling et al, 1977;Vaneeckhaute et al, 2016). The slow release rate of OMF P may provide greater opportunities for improved crop uptake.…”
Section: Fertilizer Application Effects On Soilmentioning
confidence: 94%
“…An earlier study by Antille et al (2014b) showed that relative extractability (Leytem et al, 2004) of OMF P was between 3 and 12%, which suggested only a small proportion of total P applied as OMF is released in plant-available form (Olsen P) within the first season. The remaining OMF P may be released over several years following soil application, as shown in related studies involving biosolids P (e.g., Kelling et al, 1977;Vaneeckhaute et al, 2016). The slow release rate of OMF P may provide greater opportunities for improved crop uptake.…”
Section: Fertilizer Application Effects On Soilmentioning
confidence: 94%
“…To assess the fertilizing potential and efficiency of new fertilisers, obtaining insights in their P release over time is of crucial importance (Vaneeckhaute et al, 2015). Since there are several methods to measure the efficiency of plant nutrient use, the interpretation of the recovery and efficient use of P applied to the soil is dependent on the definitions adopted and whether crop yield, P uptake or soil data are used in the calculation, (Syers et al, 2008).…”
Section: System and Synthetic Biology For Improving Biological P Recomentioning
confidence: 99%
“…Since there are several methods to measure the efficiency of plant nutrient use, the interpretation of the recovery and efficient use of P applied to the soil is dependent on the definitions adopted and whether crop yield, P uptake or soil data are used in the calculation, (Syers et al, 2008). In general, the performance of a fertiliser can be evaluated by (i) product fractionation, (ii) biological plant response assessment and/or (iii) chemical extractions of soil-fertiliser mixtures (Vaneeckhaute et al, 2015). The fractionation of fertiliser products (i) based on the solubility of P uses different solvents with a variety of strength and C E-mail address: f.delvigne@ulg.ac.be (F. Delvigne).…”
Section: System and Synthetic Biology For Improving Biological P Recomentioning
confidence: 99%
“…PUE refers to the increment in soil P status by applying bio-based fertilizers compared to the increment caused by applying chemical fertilizer (Vaneeckhaute et al, 2016). The microbial analyses showed important differences for all treatments (Table 6).…”
Section: Pot Experimentsmentioning
confidence: 99%